Modal analysis for three dimensional frame structures element using FEM - Hoang Trung Hien; Chuong Thiet Tu; Nguyen Hoai Son (Journal of Technical Education Science, 2013)
The dynamic analysis is a necessity in the design, manufacturing and maintenance of structures. The analytic solutions are not available for most practical cases and the Finite Element Method (FEM) is not reliable due to the joint problem, unclear loading, material properties and numerical error. It was proposed to find the several important modes of resonance peak for these fixed type structures. Furthermore, it is expected that the analysis method and the data in this study can be applied to a dynamic design and dynamic performance evaluation. In this paper, we present a way to find modes shape of 3D Frame by FEM program using Matlab.